EFFECTIVE MANAGEMENT OF HUMAN RESOURCE IN SCHOOLS OF THE FUTURE: THE SUPERLEADERSHIP PARADIGM - Dato Dato; Hussein Hussein; Ahmad Ahmad (Jurnal Administrasi Pendidikan, 2009)
The impact of technology on education has generated varying possibilities of approaches and techniques in the teaching-learning process in the Malaysian educational setting. In effect, the impact has been pervasive in the management and administrative culture in schools to the extent that there is a growing demand toward a continual building of competency, capacity and capability of educational leaders and managers through various training programs